Investigation of Effect of Pore Shape, Position and Passivation on the Thermoelectric Properties of Porous Armchair Silicene Nanoribbons - Kumari, Rajneesh; Randhawa, Deep Kamal Kaur; Kaur, Sukhdeep (Asian Journal of Engineering and Applied Technology, 2019)
In this paper, thermoelectric properties of porous armchair silicene nanoribbons (ASiNRs) have been investigated as a function of pore shape, position and passivation using the Non-equilibrium Green’s function (NEGF) method and Extended Huckel Technique (EHT). Here, nanopores of circular, rectangular, rhombus and triangular nature at different positions have been incorporated with an intention to optimize the structure for maximum thermoelectric figure of merit. In addition, the effect of passivation of the pore edges on the thermoelectric performance has been studied for all the shapes. Further, the effect of temperature variation on the thermoelectric efficiency has been studied. Ballistic transport regime and semi-empirical method using Huckel basis set are used to obtain the electrical properties, while the Brenner potential is used for the phononic system.